Aplikasi Trip Planner Wisata Jawa Timur Menggunakan Metode Content Based dan Collaborative Based pada Android - Edo, Fransisco; Handojo, Andreas; Palit, Henry Novianus (Jurnal Infra, 2016)
Tourism is an activity which is done by one or many persons for having holiday or recreation. Finding a good tourism spot, which fits with oneâs interest and spare time, is not an easy task. In general, tourism information that appears on the websites or in the mobile applications is not based on users interest. Lack of information is a hassle for someone who is having holiday.Therefore, a recommendation-system application was made using content-based and collaborative-based methods as a means to choose tourism spots in accordance with users preferences This Android application has features to list tourist spots which suit the users preferences give some alternate routes to user, show details of the tourism spots, and show their locations in the map.From the conducted test, the system can recommends tourism spotsthat match with userâs preferences, and user can see the recommended alternate routes and the detailed information of the tourist spots.